Effect Of Transition Taper Length On Air-Filled Substrate Integrated Waveguide Losses - Yassine Mahamat, Ibrahim Mahamat (Universiti Sains Malaysia, 2022)
The SIW structure has been enhanced by using air as the propagation medium in order to reduce losses and increase its power-handling capacity. This transition connects dielectric structures to air structures. Improving SIW performance requires the development of a low-loss dielectric-to-air transition. Using the Ansys HFSS software, this research will investigate the effects of transition taper length on air-filled substrate Integrated Waveguide Losses as well as how regression can be used to look at the link between length and losses. To further decrease transition losses, the linear spline function is used to determine the transition taper's shape. The width of the dielectric filled SIW is W, whereas the width of the air-filled SIW is W2, and the total width of the air-filled component is W1. For the period of the transition, L, the width of the taper, W2, rises while the widths of the transition taper, a and b, stay constant. The transitions exhibit the following structural characteristics: L is 30 millimetres and h is 0.508mm. Utilize the four fixed values of 30, 25, 20, and 15 mm to produce a set of curves that characterise the form of the taper in the simulation. In general, a transition length of 30 mm is deemed to result in acceptable losses. At the V-band and W-band frequencies, the Er on the Roger RT/Duroid 6002 substrate switches from dielectric to air-filled SIW. When the transition length is 15 millimetres, v-band return loss is greater than w-band return loss. The V-band has a lower return loss than the w-band at a 20 mm transition length, and the 25- and 30-mm return losses are similar. This study shows how to reduce transition duration while retaining signal quality. The data might be used to develop a smaller, better microwave device that can be worn.